EXPLORING THE CONTRIBUTION OF THE FOUR PILLARS OF PARTNERSHIP TO THE IMPLEMENTATION OF WORK-BASED LEARNING IN VOCATIONAL EDUCATION - Ardani Ahsanul Fakhri; BZ. Septeiyawan Abdullah; Muhammad Ibnu Rusydi (Department of Mechanical Engineering Education, 2026)
This study analyzes the influence of the four pillars of partnership on the success of WBL as well as the differences in perceptions between teachers, students, and industry in Tegal Regency. The method used in this study is quantitative with data analysis using multiple linear regression and one-way ANOVA. The results of the study show that the four pillars are simultaneously influential. Partially, Confidence (p = 0.002; Beta = 0.415) and Profit (p = 0.014; Beta = 0.310) is significant, while Need (p = 0.065) and Strength (p = 0.254) are not. ANOVA revealed significant differences in perceptions between groups (p = 0.008), with teachers being more optimistic than industry (mean difference = 4.200; p = 0.012). The results of the analysis show that the success of WBL is not enough to rely solely on MoUs or facilities, but is highly dependent on industry trust and mutual benefits. Schools need to build the character and safety of students' work and create a clear benefit-sharing scheme.